(untitled) (Research, Society and Development, 2024)
Even in contemporary times, despite well-established protocols for the management of anaphylaxis in pediatric emergencies, patients are often treated with second-line medications, primarily due to healthcare professionals’ reluctance to administer epinephrine. Furthermore, this condition is frequently underdiagnosed, given the possibility of an atypical clinical presentation in the pediatric age group and the difficulty for patients, families, and healthcare professionals in recognizing the symptoms. Underreporting also persists as a reality, making it challenging to obtain accurate data on the prevalence of this condition. This study aims to identify the factors contributing to the inadequate management of anaphylaxis in the pediatric age group and delineate the necessary measures to reverse this situation. This is an integrative literature review, conducted according to PRISMA methodology, utilizing PubMed and SciELO article platforms, with a publication date limit of the last 5 years, searching for articles from studies conducted in both developed and developing countries, with the keywords “anaphylaxis,” “emergency,” and “pediatrics” in Portuguese and English. It was found that in the pediatric population, the main predisposing factors for the inadequate management of this condition include primarily underdiagnosis and the preferential use of known second-line medications. Part of this problem stems from the failure to recognize the clinical condition and another part from medical concerns about the possible side effects of epinephrine.